2016
DOI: 10.1111/papt.12099
|View full text |Cite
|
Sign up to set email alerts
|

Young children's experiences of living with a parent with bipolar disorder: Understanding the child's perspective

Abstract: Objectives To explore the experiences of young children of living with a parent with bipolar disorder (BD) and how this impacts on their emotional well‐being. Design Qualitative study using a computer‐assisted semi‐structured interview, ‘In My Shoes’ (IMS). Methods Ten children aged between 4 and 10 years with a parent with BD identified via self‐help groups were interviewed about their experience of family life. Thematic analysis was used following transcription. Results Four main themes emerging from themati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
1
16
0
1
Order By: Relevance
“…Findings from this study are consistent with previous studies regarding children and adult children’s hypersensitivity to and for parental emotions, when their parent presented with mental illness [ 1 , 29 ]. However, this study extended this knowledge to suggest that adult children who had lived with childhood parental mental illness, also experienced a similar hypersensitivity to their own children’s emotions, possibly resulting in their own parenting anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…Findings from this study are consistent with previous studies regarding children and adult children’s hypersensitivity to and for parental emotions, when their parent presented with mental illness [ 1 , 29 ]. However, this study extended this knowledge to suggest that adult children who had lived with childhood parental mental illness, also experienced a similar hypersensitivity to their own children’s emotions, possibly resulting in their own parenting anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…They are sensitive to cues discouraging conversations about parental mental illness and might conceal their worries and questions, so as not to burden their family further (Van Parys et al, 2015). Younger children, especially, are more dependent on others to reach out to them (Mordoch & Hall, 2008) and are likely to blame themselves for their parent’s illness (Backer, Murphy, Fox, Ulph, & Calam, 2017). So while being able to create distance from an acutely distressed parent might benefit the child, it might be important for parents to also provide an appropriate explanation of the situation and keep parent–child communication open and ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the expansion of screening panels from only a few to dozens of disorders. Since then it has been documented that parental education about NBS is not effective; parents are not receiving the information or are unware about screening and its principal aspects [9][10][11][12]. The last trimester of pregnancy has been suggested as the optimal period for information provision [1], but a survey carried out among EU member states revealed that 45% of them inform parents only after birth at the time of blood sampling [6].…”
Section: Introductionmentioning
confidence: 99%